Quality of life measures in Italian children with atopic dermatitis and their families - Monti Fiorella; Agostini Francesca; Gobbi Francesca; Neri Erica; Schianchi Sandra; Arcangeli Fabio (BMC, 2011)
Abstract Background The impact of atopic dermatitis (AD) on children's quality of life (QoL) in US and European countries is relatively well known, though rarely evaluated in the Italian population. Moreover, the association between child age and QoL has not been enough investigated, even though few studies detected a worse QoL in youngest AD children. The aim of the study was to evaluate the QoL in an Italian sample of atopic children and their families, also exploring a possible association with child age. Methods 60 AD children aged between 1-12 years and their mothers completed specific QoL questionnaires (IDQoL/CDLQI, DFI) and a clinician completed a measure of AD severity (SCORAD). Results AD severity (Objective SCORAD) significantly correlated with QoL measures. Severe AD children showed higher IDQoL/CDLQI and DFI scores compared to mild and moderate AD groups (P = 0.006 and P < 0.0005, respectively), but only DFI scores differed in these last two conditions (P = 0.014). DFI scores negatively correlated with children's age (P = 0.046), but did not differ when considering child age ranges. Multiple linear regression analyses revealed a significant association between Objective SCORAD and QoL measures. Conclusions A strong association between severe AD and poor QoL, both in children and mothers, was found in the Italian sample, in line with the international literature. Family's QoL scores were sensitively related to AD severity, more than the child's QoL, emphasising that the disease has a deep impact on the family. A significant association between age and QoL was only partially found and needs further investigation.